Turning on the light within: subcortical nuclei of the isodentritic core and their role in Alzheimer's disease pathogenesis - Theofilas, Panos (J Alzheimers Dis, 2015)
Pharmacological interventions in Alzheimer's disease (AD) are likely to be more efficacious if administered early in the course of the disease, foregoing the spread of irreversible changes in the brain. Research findings underline an early vulnerability of the isodendritic core (IC) network to AD neurofibrillary lesions. The IC constitutes a phylogenetically conserved subcortical system including the locus coeruleus in pons, dorsal raphe nucleus and substantia nigra in the midbrain, and nucleus basalis of Meynert in basal forebrain. Through their ascending projections to the cortex, the IC neurons regulate homeostasis and behavior by synthesizing aminergic and cholinergic neurotransmitters. Here we reviewed the evidence demonstrating that neurons of the IC system show neurofibrillary tangles in the earliest stages of AD, prior to cortical pathology, and how this involvement may explain pre-amnestic symptoms, including depression, agitation and sleep disturbances in AD patients. In fact, clinical and animal studies show a significant reduction of AD cognitive and behavioral symptoms following replenishment of neurotransmitters associated with the IC network. Therefore, the IC network represents a unique candidate for viable therapeutic intervention and should become a high priority for research in AD.